The Impacts of Folklore on the rhetorical language in Mala Khalil Mashakhti’s Poems - Nabe, Jutyar I.; Ahmed, Dawlat M.; Khaleel, Kawan I. (Humanities Journal of University of Zakho, 2018)
This research study tackles the effects of Folklore on the rhetorical language in Mala Khalil Mashakhti’s poems where all the types of genres of this folklore and its branches were discussed taking into consideration the political and social circumstances experienced by the poet. This is because they were the reason for the appearance of his poems through which the folklore spread in a broad way. Therefore, this study is considered an introduction and an attempt to study any topic related to Folklore along with analysing the poetical genres of the poet and the way of dealing with it in poetry.